Scientific Opinion on Flavouring Group Evaluation 67, Revision 3 (FGE.67Rev3): consideration of 23 furan‐substituted compounds evaluated by JECFA at the 55th, 65th, 69th and 86th meetings. (3rd February 2021) - ,; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Engel, Karl‐Heinz; Fowler, Paul; Frutos Fernandez, Maria Jose; Fürst, Peter; Gundert‐Remy, Ursula; Gürtler, Rainer; Husøy, Trine; Manco, Melania; et al.
Abstract: The Panel on Food Additives and Flavourings (FAF) was requested to consider the JECFA evaluations of 25 flavouring substances assigned to the Flavouring Group Evaluation 67 (FGE.67Rev3), using the Procedure as outlined in the Commission Regulation (EC) No 1565/2000. Eleven substances have already been considered in FGE.67 and its revisions (FGE.67Rev1 and FGE.67Rev2). During the current assessment, two substances were no longer supported by industry, therefore 12 candidate substances are evaluated in FGE.67Rev3. New genotoxicity and toxicity data are available for 2‐pentylfuran [FL‐no: 13.059] and 2‐acetylfuran [FL‐no: 13.054], which are representative substances of subgroup IV [FL‐no: 13.069, 13.106, 13.148] and VI‐B [FL‐no: 13.045, 13.070, 13.083, 13.101, 13.105, 13.138, 13.163], respectively. Based on these data, the Panel concluded that the concern for genotoxicity is ruled out for both [FL‐no: 13.054] and [FL‐no: 13.059] and consequently for the substances that they represent. Since the candidate substances cannot be anticipated to be metabolised to innocuous products only, they were evaluated along the B‐side of the Procedure. The Panel derived a NOAEL of 22.6 mg/kg bw per day and a BMDL of 8.51 mg/kg bw per day, for 2‐acetylfuran and 2‐pentylfuran, respectively. For all 12 substances sufficient margins of safety were calculated when based on the MSDI approach. Adequate specifications for the materials of commerce are available for all 23 flavouring substances. The Panel agrees with JECFA conclusions, for all 23 substances, 'No safety concern at estimated levels of intake as flavouring substances' based on the MSDI approach. For 18 substances [FL‐no: 13.021, 13.022, 13.023, 13.024, 13.031, 13.045, 13.047, 13.054, 13.059, 13.074, 13.083, 13.101, 13.105, 13.106, 13.138, 13.148, 13.163 and 13.190], the mTAMDI intake estimates are above the threshold of toxicological concern (TTC) for their structural classes and more reliable data on uses and use levels are required to finalise their evaluation.